Synthesis of Micromesoporous Zeolite-Alumina Catalysts for Olefin Production from Heavy Crude Oil - M. Al-Samhan; J. Al-Fadhli; A. M. Al-Otaibi; R. Bouresli (International Journal of Chemical Engineering)
Maximizing the production of high-value olefins from heavy crude oil is a crucial topic in the downstream refining industry. However, converting heavier fractions is a major challenge due to the small pore size of the zeolites. Therefore, this work aimed to develop extrudate zeolite catalysts posing adequate micromesoporous pore network and moderate acidity by combining microporous zeolite with the boehmite phase of alumina. These extruded zeolite-alumina catalysts are expected to allow sufficient diffusion of heavy fractions, thus leading to high cracking of heavy oil into valuable olefins. Different zeolite-alumina catalysts of varying alumina content ranging from 25 to 75% (AlZ-25, AlZ-50, and AlZ-75) were prepared in the laboratory to study the optimum zeolite-alumina ratios for maximum olefin production from heavy oil. The catalysts were characterized for their chemical and physical properties using nitrogen adsorption (N2 adsorption), X-ray diffraction (XRD), inductively coupled plasma (ICP) spectrometry, Fourier transform infrared (FT-IR) spectroscopy, and NH3 temperature programmed desorption (TPD). A gradual increase in the average pore diameter (APD) of the catalysts was observed due to the alumina ratio with a distinct range of acidity that is in the range of 125 to 375°C, and also the geometry of pores is not the same for all of the supports. Catalytic performance tests were conducted in a fixed-bed reactor at 450°C, 10 bar, and liquid hourly space velocity (LHSV) of 1 h−1. The results revealed that the prepared catalysts were thermally stable and effective in heavy oil conversion to olefins. Moreover, the selectivity of propylene was higher than that of ethylene (P/E) due to the modified textural and acidic properties of the catalysts. The results showed that the catalysts prepared with moderate acidity and adequate mesopores exhibited a considerable effect on the conversion of heavy crude oil into olefins. Hence, the acidity and mesoporosity of the catalysts play a vital role in determining the catalyst performance.